CHARACTERISTICS OF PATIENTS WITH DIABETES MELLITUS TYPE 2 THAT WAS HOSPITALIZED IN PATAR ASIH HOSPITAL DELI SERDANG REGENCY - Dita Indra Novitasari (Jambura Journal of Health Sciences and Research, 2022)
Hasil Riskesdas 2018 menunjukkan prevalensi diabetes melitus di Indonesia berdasarkan diagnosis dokter umur ≥ 15 tahun sebesar 2%. Angka ini menujukkan peningkatan prevalensi dari tahun 2013 yang sebelumnya 1,5%. Kebaruan penelitian karena meneliti karakteristik pasien DM tipe 2 rawat inap di Rumah Sakit Patar Asih Kabupaten Deli Serdang. Tujuan penelitian untuk mengetahui karakteristik pasien DM tipe 2 rawat inap di Rumah Sakit Patar Asih Kabupaten Deli Serdang Sumatera Utara. Metode penelitian menggunakan desain studi kasus bersifat deskriptif dan retrospektif. Hasil penelitian jenis kelamin laki-laki tertinggi sebanyak 25 orang (62,5%). Umur terbanyak ≥35 tahun sebanyak 36 orang (90,0%). Keluhan utama terbanyak nyeri pada kaki/bengkak/luka dan penglihatan kabur sebanyak 8 orang (20,0%), jenis pekerjaan terbanyak pensiunan/ibu rumah tangga dan PNS/TNI/Polisi sebanyak 11 orang (27,5%). Kadar Hb.A1c terbanyak tidak normal (6,5%) sebanyak 28 orang (70,0%). Kadar gula darah sewaktu 400-500mg/dl sebanyak 19 orang (47%). Rutin kontrol paling banyak 24 orang (60%). Lama rawatan 4-7 hari sebanyak 29 orang (72.5%). Medikamentosa terbanyak adalah obat hipoglikemik oral sebanyak 37 orang (92.5%). Komplikasi terbanyak adalah retinopati DM sebanyak 10 orang (25%). Keadaan sewaktu pulang terbanyak adalah pulang berobat jalan sebanyak 36 orang (90%). Kesimpulannya jenis kelamin terbanyak laki-laki, umur≥35 tahun, keluhan utama nyeri pada kaki/bengkak/luka dan pengelihatan kabur, jenis pekerjaan yaitu tidak bekerja/pensiunan/ibu rumah tangga dan PNS/TNI/Polisi, kadar HbA1c terbanyak tidak normal, kadar gula darah sewaktu 400-500mg/dl, paling banyak pasien rutin kontrol, medikamentosa terbanyak obat hipoglikemik oral, komplikasi terbanyak retinopati DM, keadaan sewaktu pulang paling banyak pulang berobat jalan.Kata kunci: Diabetes; Prevalensi; Medikamentosa; Retinopati.AbstractThe results of Riskesdas 2018 show that the prevalence of diabetes mellitus in Indonesia based on a doctor's diagnosis aged 15 years is 2%. This figure shows an increase in prevalence from 2013 which was previously 1.5%. The novelty of the study is that it examines the characteristics of type 2 DM patients hospitalized at Patar Asih Hospital, Deli Serdang Regency. The purpose of the study was to determine the characteristics of type 2 DM patients hospitalized at Patar Asih Hospital, Deli Serdang Regency, North Sumatra. The research method using a case study design is descriptive and retrospective. The results of the study were the highest male sex as many as 25 people (62.5%). The highest age was 35 years as many as 36 people (90.0%). The main complaints were mostly pain in the legs/swelling/injury and blurred vision as many as 8 people (20.0%), the most types of work were retirees/housewives and civil servants/TNI/police as many as 11 people (27.5%). Most Hb.A1c levels were abnormal (6.5%) as many as 28 people (70.0%). Blood sugar levels at 400-500mg/dl were 19 people (47%). Routine control is at most 24 people (60%). The length of treatment was 4-7 days as many as 29 people (72.5%). Most medications were oral hypoglycemic drugs as many as 37 people (92.5%). The most complications were DM retinopathy as many as 10 people (25%). The situation when they returned home was mostly outpatient as many as 36 people (90%). In conclusion, most of the sexes are male, age 35 years old, the main complaint is pain in the legs/swelling/wounds and blurred vision, the type of work is not working/retired/housewife and civil servant/TNI/police, most HbA1c levels are abnormal, blood sugar levels at 400-500mg/dl, most patients were routinely controlled, the most medication was oral hypoglycemic drugs, the most complications were DM retinopathy, the condition when returning home was mostly outpatient.